Does Venture Capital Investment Spur Employment Growth? - Ansgar Belke; Rainer Fehn; Neil Foster (Center for Economic Studies and ifo Institute (CESifo), 2003)
Anglo-Saxon countries have been successful in the 1990s concerning labor market performance compared to the former role models Germany and Japan. This reversal in relative economic performance might be related to idiosyncracies in financial markets with bank-based financial markets as in Germany and Japan being possibly inferior to stockmarket based financial markets in turbulent times and when approaching the economic frontier. A cleavage is related to venture capital markets which are flourishing on Anglo-Saxon but not on German type financial markets. Venture capital is crucial for financing structural change, new firms and innovations and therefore possibly also nowadays for employment growth.
Keywords: 330; labor markets; venture capital; unemployment; new economy; panel data analysis